Psychiatry gamification from blended learning models and efficacy of this program on students - Leili Mosalanejad; Saeed Abdollahifard; Tahereh Abdian (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: New gamification technology with a detailed understanding of the goals and prospects, and with the help of game elements and techniques, leads to promotion of motivation and participation, and ultimately behavior change. Therefore, this study aimed to evaluate the implementation of a mental gamification from blended learning based on the flex model and efficacy of this program on students. METHODS: In this study, with the design of mental illness lessons for undergraduate and executive groups, using flex model, two parts of technical and educational design were used. In the technical section, three parts on dynamics, mechanisms, and elements of gaming were considered. Intervention was studied on different groups of medical students including medical, health, and laboratory sciences. Effect of this educational program and its impact on their students' learning, motivation, and satisfaction was studied using quantitative and qualitative analyses. RESULTS: The results of the students' prospective about the efficacy of the method showed that the mean scores of most of the items were higher than the average. This implies that students' attitude toward using gamification was positive. In the other part, the qualitative results of the study were analyzed and the students' analysis of their advantages and disadvantages and their perceptions on the impact of the intervention was examined. CONCLUSION: Based on the flex model, mental gamification based on blended learning is effective in shaping the students' satisfaction.